From Heritage to Commerce: Utilizing Space Syntax to Optimize Visibility for Retail interior design in Al-Turaif’s Touristic Landscape (المجلة الدولية للبحوث العلمية, 2025)
This study investigates retail visibility within the heritage tourism context of Al-Turaif district, Saudi Arabia, applying Space Syntax theory including isovist analysis, axial mapping, and Visibility Graph Analysis (VGA) to examine both outdoor and indoor visual and navigational possibilities. It aims to explore how Najdi interior design concepts can be integrated into Culture Concept Stores to enhance spatial connectivity, product visibility, and visitor attraction. The research draws on extensive spatial mapping, many qualitative interviews with stakeholders, site observations, and visitor feedback. At the macro level, the study assesses how retail locations influence visitor patterns, storytelling, and engagement within the broader heritage site. Locally, it analyzes interior spatial connectivity, external sightlines, zoning effectiveness, and commercial performance. Findings reveal that enhancing spatial visibility consistently supports cultural authenticity and visitor demand while preserving traditional aesthetics. The study culminates in a practical design framework that aligns traditional architectural identity with retail functionality. This framework serves as a valuable tool for urban designers, heritage site managers, and policymakers seeking to balance cultural preservation with economic viability, ultimately boosting both the cultural and economic value of heritage tourism destinations.